Dimensionality of hallucinatory predisposition: Confirmatory factor analysis of the Launay-Slade Hallucination Scale-revised in college students - Fonseca-Pedrero, Eduardo; Lemos-Giráldez, Serafín; Paino, Mercedes; Sierra-Baigrie, Susana; Villazón-García, Úrsula; García-Portilla González, Paz; Muñiz, José (Anales de Psicología / Annals of Psychology, 2010)
Hallucinatory predisposition, as measured by the Launay-Slade Hallucination scale-revised (LSHS-R) (Bentall & Slade, 1985), is a multi-dimensional construct, although its factor structure is not yet well estab-lished. The purpose of this work was to analyze the dimensional structure of hallucinatory predisposition in nonclinical population. The sample comprised 807 young adults, 562 female (63.3%), with a mean age of 20.19 (SD = 2.98). The results showed that the LSHS-R presented ade-quate psychometric properties. Cronbach’s alpha coefficient reached 0.90. The confirmatory factor analyses conducted indicated that Waters et al. ‘s (2003) three-factor model and Levitan et al.‘s (1996) four-factor model were those that showed the best fit to the data in comparison to the alter-native proposed models. These data confirm the multidimensional nature of hallucinatory predisposition as measured by the LSHS-R. Future studies should continue to investigate the dimensions underlying the LSHS-R in clinical and nonclinical populations and examine its invariance across participants’ gender and age.